(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article highlights the development of Teacher Assessment Literacy (TAL) in relation to international English testing systems such as IELTS, TOEFL and CEFR-based frameworks. It points out the significant role of teachers’ understanding of marking standarts in making sure alignment in the middle of classroom practices and global standarts.The paper explores usual problems educators face in creating legal and trustworthy assessments as well as underlines the need for constant professional growth to enhance TAL.